Penggunaan Video Ekosistem Sebagai Sarana Pembelajaran Pada Masa Pandemi Covid-19 di Sekolah Dasar - Didik Tri Setiyoko; Juhadi Juhadi (Peneliti.net, 2023)
Abstract The purpose of this study was to describe the use of ecosystem videos during the covid-19 pandemic in elementary schools, to find out the importance of using ecosystem videos for students during the covid-19 pandemic in elementary schools, and to describe the meaning of ecosystem videos for students in elementary schools. . This study uses a qualitative research approach with research design using case studies. Data collection techniques using non-participant observation, interviews and documentation. The validity of the data is done by triangulation. The triangulation used in this research is source triangulation and technique triangulation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. The use of video ecosystem is important for students to attract attention and direct the concentration of students because video is a moving image that is said to be more effective than other media. And the meaning of the video ecosystem for students, human teachers (actors) who act important on the basis of the meaning of giving students enthusiasm for learning and providing actions that are obtained through social interaction.